2016
DOI: 10.4103/0976-237x.188586
|View full text |Cite
|
Sign up to set email alerts
|

Intraosseous verrucous carcinoma arising from an orthokeratinized odontogenic keratocyst: A report of a rarest entity

Abstract: Intraosseous verrucous carcinomas (VCs) arising from odontogenic cysts are a rare entity. An unusual case of a VC arising from the orthokeratinized odontogenic cyst is described for the first time. The microscopic features of the lesion are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Bodner et al reviewed 116 cases of PIOSCC [ 7 ]. However, VC arising from OC is very rare, with only seven cases reported to date (Table 1 ) [ 2 , 4 , 8 , 18 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bodner et al reviewed 116 cases of PIOSCC [ 7 ]. However, VC arising from OC is very rare, with only seven cases reported to date (Table 1 ) [ 2 , 4 , 8 , 18 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peng et al summarized all reports regarding VC and explained that since PIOVC has no recurrence or metastasis, it does not require any forms of neck dissection, and removal of primary lesion alone can lead to good prognosis. The seventh case was reported by Kamarthi et al in 2016, on VC at OC in the maxilla with confirmed verrucous transformation of the cystic lining [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…They show male preponderance (4 : 1) and are more common in the maxilla as compared to the mandible. Anterior maxilla has been reported to be affected more commonly [18]. …”
Section: Discussionmentioning
confidence: 99%
“…Verrucous proliferation in a cystic lining is one such rarity. To the best of our knowledge only eight cases of odontogenic cysts with verrucous proliferation have been reported in English literature [18], of which six were reported as verrucous carcinomas arising in odontogenic cysts. We describe a case of an infected odontogenic cyst exhibiting verrucous proliferation and melanin pigmentation.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Reviewing English literature, to the best of our knowledge, there are only 3 cases of PIOC arising in OOC to date. 3 , 4 , 5 OOC accounts for about 1% of all odontogenic cyst, and it is considered as less aggressive than OKC with less than 2% in recurrent rate. Although malignant transformation of odontogenic cyst is rare, the pathologists should carefully examine the differentiation pattern of cystic epithelial lining.…”
mentioning
confidence: 99%